Steam generation from biomass : construction and design of large boilers - Vakkilainen, Esa (Butterworth-Heinemann, 2017)
Steam Generation from Biomass: Construction and Design of Large Boilers provides in-depth coverage of steam generator engineering for biomass combustion. It presents the design process and the necessary information needed for an understanding of not only the function of different components of a steam generator, but also what design choices have been made. Professor Vakkilainen explores each particular aspect of steam generator design from the point-of-view of pressure part design, mechanical design, layout design, process design, performance optimization, and cost optimization. Topics such as fuels and their emissions, steam-water circulation, auxiliary equipment, availability and reliability, measurements and control, manufacture, erection, and inspection are covered. Special attention is given to recovery boilers and fluidized bed boilers, and automated design and dimensioning calculation spreadsheets are available for download at the book's companion website. This book is intended for both design engineers and steam boiler operators, as well as those involved in plant management and equipment purchasing.